The role and position of passive intervertebral motion assessment within clinical reasoning and decision-making in manual physical therapy: a qualitative interview study - van Trijffel, Emiel (Maney Publishing, 2010)
Passive intervertebral motion (PIVM) assessment is a characterizing skill of manual physical therapists (MPTs) and is important for judgments about impairments in spinal joint function. It is unknown as to why and how MPTs use this mobility testing of spinal motion segments within their clinical reasoning and decision-making. This qualitative study aimed to explore and understand the role and position of PIVM assessment within the manual diagnostic process. Eight semistructured individual interviews with expert MPTs and three subsequent group interviews using manual physical therapy consultation platforms were conducted. Line-by-line coding was performed on the transcribed data, and final main themes were identified from subcategories. Three researchers were involved in the analysis process. Four themes emerged from the data: contextuality, consistency, impairment orientedness, and subjectivity. These themes were interrelated and linked to concepts of professionalism and clinical reasoning. MPTs used PIVM assessment within a multidimensional, biopsychosocial framework incorporating clinical data relating to mechanical dysfunction as well as to personal factors while applying various clinical reasoning strategies. Interpretation of PIVM assessment and subsequent decisions on manipulative treatment were strongly rooted within practitioners’ practical knowledge. This study has identified the specific role and position of PIVM assessment as related to other clinical findings within clinical reasoning and decision-making in manual physical therapy in The Netherlands. We recommend future research in manual diagnostics to account for the multivariable character of physical examination of the spine.